(untitled) (Journal of Computational Mathematics, 1984)
In this paper we consider the nonlinear operator equation λ x=Lx+G(λ,x) where L is a closed linear operator of X-›X, X is a real Banach Space, with a simple eigenvalue λ_0 eq 0. We discretize its Liapunov-Schmidt bifurcation equation instead of the original nonlinear operator equation and estimate the approximating order of our approximate solution to the genuine solution. Our method is more convenient and more accurate. Meanwhile we put forward several abstract Newton-type iterative schemes, which are more efficient for practical computation, and get the result of their super-linear convergence.